Tackling fuel poverty through household advice and support: Exploring the impacts of a charity-led project in a disadvantaged city in the United Kingdom. (December 2020) - Ramsden, Sam
Abstract: This article explores the impacts of a charity project which aimed to help people vulnerable to fuel poverty improve their energy efficiency and reduce energy costs, through providing energy monitors and advice at a household-level. The research makes an important contribution to emerging but scarce research on how charities can help households vulnerable to fuel poverty. Interviews were conducted with 40 participants and 32 participants described how the project helped them (through one or a combination of the following): reduce inefficient energy use; switch tariffs; change from pre-payment meters; apply for subsidies for vulnerable people; and/ or improve their confidence to manage their household energy needs. Nineteen of the participants were vulnerable to fuel poverty and fifteen of these estimated that the project helped them save money. While achieving financial savings was the key motivation for participants, 15 households described that they participated in the project to reduce their CO2 emissions. However, the approach was limited and the impacts could have been increased through energy audits, property-level energy efficiency improvements, and support to raise issues with housing providers. The research argues that household-level face-to-face advice and support can help people vulnerable to fuel poverty and charities can operate effectively in a space between the government, energy companies, local authorities and households to provide this support. However, charities need access to technical expertise, reflexive funding, and effective coordination with local authorities to improve their long-term impact.